Nematicity in a cuprate superconductor revealed by angle-resolved photoemission spectroscopy under uniaxial strain - S. Nakata (Nature Portfolio, 2021)
Abstract The nature of the pseudogap and its relationship with superconductivity are one of the central issues of cuprate superconductors. Recently, a possible scenario has been proposed that the pseudogap state is a distinct phase characterized by spontaneous rotational symmetry breaking called “nematicity” based on transport and magnetic susceptibility measurements, where the symmetry breaking was observed below the pseudogap temperature T ∗. Here, we report a temperature-dependent ARPES study of nematicity in slightly overdoped Bi1.7Pb0.5Sr1.9CaCu2O8+δ triggered by a uniaxial strain applied along one of the Cu–O bond directions. While the nematicity was enhanced in the pseudogap state as in the previous studies, it was suppressed in the superconducting state. These results indicate that the pseudogap state is characterized by spontaneous rotational symmetry breaking and that the nematicity may compete with superconductivity. Relationship between the nematicity and charge-density waves, both of which are observed in the pseudogap state, is discussed.